Diseño e implementación de una herramienta software para evaluar el estado del índice de obsolescencia para los equipos biomédicos del Hospital Universitario San José de Popayán (2021)
The assessment of obsolescence of medical equipment in health care institutions is an extremely important process, as it provides knowledge based on real indicators about the state of the equipment that is part of each service. The obsolescence index is an objective tool for evaluating the current state of biomedical equipment, used as an instrument to support decision-making in biomedical technology management. For the development of this project, it is proposed to quantify the obsolescence index based on the "Guide for filling out the proposal for the biomedical equipment obsolescence index", proposed by the Ministry of Health in 2017 and consequently a software tool is developed in Wordpress, as a digital support that allows a dynamic process of treatment of the established parameters, according to the needs of the hospital, resulting in a qualitative scale of the obsolescence index, identifying whether the equipment needs replacement or renewal depending on the obsolescence score obtained. This work includes the technology available in the areas of: Intensive Care Unit, Intermediate Care Unit including the Covid areas and as interdependence, the surgery area of the HUSJ Finally, through the development of this proposal, a survey of technical, clinical and economic data of the biomedical equipment of the mentioned areas is achieved and through the software tool created, it is possible to have this information in a fast, organised way and with some distinctive statistical data for each area. It also allows the entry and/or import of new data/equipment into the system and its respective calculation of the obsolescence index.